POTENSI SITUS ARKEOLOGI KAWASAN KERINCI, JAMBI: IKON BUDAYA AUSTRONESIA - Aziz, Fadhila Arifin (AMERTA, 2010)
ABSTRAK Kawasan Kerinci merupakan salah satu lokasi yang memiliki keanekaragaman warisan budaya masa lampau. Secara administrative, kawasan ini berada di Kabupaten Kerinci, Provinsi Jambi. Wilayah ini pada masa sekarang masih tergolong daerah terpencil akibat sarana transportasi dan komunikasi yang terbatas. Kondisi geografis yang bergunung dan berbukit dengan danau dan anak-anak sungai merupakan faktor penyebab utama sektor pertanian (berladang, berkebun) menjadi andalan pendapatan daerah. Informasi tentang sumberdaya arkeologi di Jambi dapat dikatakan sangat sedikit dijumpai, baik dalam buku pelajaran sekolah, leaflet informasi budaya dan pariwisata, maupun yang dikeluarkan pemerintah daerah atau lembaga terkait di pusat. Namun cukup membuktikan bahwa daerah Jambi memiliki potensi sumberdaya budaya materi sejak masa prasejarah (mesolitik) sampai masa kolonial. Salah satu wilayah Jambi, yaitu di kawasan sekitar Danau Kerinci, sampai kini masih dijumpai bukti sumberdaya budaya materi yang memiliki karakter dari masa prasejarah. Oleh karena itu penelitian untuk mengungkapkan sejarah asal budaya di Jambi dalam hubungannya dengan penutur dan budaya Austronesia menjadi penting untuk dikaji dengan perspektif arkeologi. Kata Kunci: Potensi situs, Kawasan, Budaya Austronesia ABSTRACT. Archaeological Sites Potential on Kerinci Region, Jambi: Icon of Austronesia Culture Kerinci region is a location that has a diversity of cultural heritages of the past. Administratively, this area is located in Kerinci Regency, Jambi Province (formerly part of west Sumatra). This area today is still relatively remote due to limited transportation and communication facilities. Geographical conditions and steep mountainous with lakes and tributaries are the main factors driving the agricultural sector (farming, gardening) as the main regional income. Informations about archaeological resources from the early history of the cultural heritage in Jambi can are very rarely found in school books, leaflet of culture and tourism information, eventhough local government or related institutional in the central. But there was supporting evidence that the area of Jambi has the potency of cultural heritage since prehistoric (Mesolithic) to the Colonial periods. In one area of Jambi, which is around Kerinci region, until now can still be found evidences of material culture with prehistoric characters. There are remains of archaeological sites in the Lakes Kerici region from prehistoric times (Mesolithic until Palaeometalic) to indicate the beginning of civilization in communities that already have the technology (equipment), social organization, beliefs and so on. Therefore, research to express the historical values of cultural origin of Jambi in connection with the Austronesian speaking and culture is important to examine using Archaeological perspectives. Key words: Sites Potential, Region, Culture of Austronesia